Color AfterImages Determined in Non-Cardinal Color Axes - Paz Filgueira, Clemente (2018)
Introduction: Complementary color afterimages appear after the removal of a bright stimulus from the visual field. Using a time-varying paradigm, Zaidi et al (Current Biology, 2012) found that adaptation within retinal ganglion cells may be sufficient to account for the appearance of color afterimages for stimuli modulating along the cardinal color axes of l (L/(L+M)) or s (S/(L+M)). The current study modulated stimuli along non-cardinal diagonal axes in MacLeod & Boynton cone chromaticity space to evaluate whether adaptation within higher order mechanisms contributes to color afterimages. Methods: Subjects (3 males and 3 females) were presented stimuli consisting of two hemidisks subtending 3.6° on an equal energy white (EEW) background (20 cd/m2). The colors of the hemidisks were modulated complementarily by sinusoidal half-cycles (1/32 Hz) along one of five axes: (1) L+M+S, (2) l, (3) s, and two non-cardinal axes that modulated l and s simultaneously with the same contrasts as those modulations along the cardinal axes. The task of the observers was to indicate the time at which the two semicircles appeared the same shade of gray (identity point) using a face clock. For each axis, we tested four contrasts (L+M+S: 12.5%-50%; l: 2.9%-6.5%; s: 35%-80%). Results: The time to reach the identity point increased linearly with stimulus contrast for all axes. The identity point was reached faster for stimuli along s-axis than for the non-cardinal axes under the same s-contrasts, whereas no difference was found between the non-cardinal and the l axes under the same l contrast. Conclusions. The time-varying afterimage for stimuli modulated along the non-cardinal color axes was determined by the cardinal mechanism with slower adaptation. This evidence indicates that adaptation within retinal ganglion cells is sufficient to account for the dynamics of color afterimages.